Pengaruh Servant Leadership dan Kepuasan Kerja terhadap Organizational Citizenship Behaviour (Studi Persepsional pada Karyawan Divisi Infrastruktur Perhubungan PT Pindad) - Reza Gina Sopia, - (2023)
This study focused on the description of Organizational Citizenship Behaviour at the Infrastruktur Perhubungan Division of PT Pindad. Organizational Citizenship Behaviour is a behaviour of someone who is not an obligation of an employee's formal job but it is very supportive in carrying out activities in the organization effectively. There are several factors that influence the OCB, but this research will focus on Servant Leadership (X1) and Job Satisfaction (X2). The purpose of this study was to find out the description of Servant Leadership, Job Satisfaction, and Organizational Citizenship Behaviour at the Infrastruktur Perhubungan Division of PT Pindad and to determine the effect of Servant Leadership on Organizational Citizenship Behaviour, the effect of Job Satisfaction on Organizational Citizenship Behaviour, and the influence of Servant Leadership and Job Satisfaction on Organizational Citizenship Behaviour at the Infrastruktur Perhubungan Division of PT Pindad. The research method used is descriptive and verificative method with a total sample of 80 respondents who are employees of the Infrastruktur Perhubungan Divison of PT Pindad. The data analysis technique used is Pearson's Correlation Coefficient, multiple linear regression, and hypothesis testing using the F-test and t-test. In this study, there are results indicating that Servant Leadership has a positive and significant effect on Organizational Citizenship Behaviour, Job satisfaction has a positive and significant effect on Organizational Citizenship Behaviour and simultaneously that Servant Leadership and Job Satisfaction have a positive and significant effect on Organizational Citizenship Behaviour at the Infrastruktur Perhubungan Division of PT Pindad Keywords: Servant Leadership, Job Satisfaction, Organizational Citizenship Behaviour